Auditory Localization and Spatial Release From Masking in Children With Suspected Auditory Processing Disorder. Issue 5 (September 2019) - Boothalingam, Sriram; Purcell, David W.; Allan, Chris; Allen, Prudence; Macpherson, Ewan
Abstract : Objectives: We sought to investigate whether children referred to our audiology clinic with a complaint of listening difficulty, that is, suspected of auditory processing disorder (APD), have difficulties localizing sounds in noise and whether they have reduced benefit from spatial release from masking. Design: Forty-seven typically hearing children in the age range of 7 to 17 years took part in the study. Twenty-one typically developing (TD) children served as controls, and the other 26 children, referred to our audiology clinic with listening problems, were the study group: suspected APD (sAPD). The ability to localize a speech target (the word "baseball") was measured in quiet, broadband noise, and speech-babble in a hemi-anechoic chamber. Participants stood at the center of a loudspeaker array that delivered the target in a diffused noise-field created by presenting independent noise from four loudspeakers spaced 90° apart starting at 45°. In the noise conditions, the signal-to-noise ratio was varied between −12 and 0 dB in 6-dB steps by keeping the noise level constant at 66 dB SPL and varying the target level. Localization ability was indexed by two metrics, one assessing variability in lateral plane [lateral scatter (Lscat)] and the other accuracy in the front/back dimension [front/back percent correct (FBpc)]. Spatial release from masking (SRM) was measured using a modified version of the Hearing in Noise Test (HINT). In this HINT paradigm, speech targets were always presented from the loudspeaker at 0°, and a single noise source was presented either at 0°, 90°, or 270° at 65 dB A. The SRM was calculated as the difference between the 50% correct HINT speech reception threshold obtained when both speech and noise were collocated at 0° and when the noise was presented at either 90° or 270°. Results: As expected, in both groups, localization in noise improved as a function of signal-to-noise ratio. Broadband noise caused significantly larger disruption in FBpc than in Lscat when compared with speech babble. There were, however, no group effects or group interactions, suggesting that the children in the sAPD group did not differ significantly from TD children in either localization metric (Lscat and FBpc). While a significant SRM was observed in both groups, there were no group effects or group interactions. Collectively, the data suggest that children in the sAPD group did not differ significantly from the TD group for either binaural measure investigated in the study. Conclusions: As is evident from a few poor performers, some children with listening difficulties may have difficulty in localizing sounds and may not benefit from spatial separation of speech and noise. However, the heterogeneity in APD and the variability in our data do not support the notion that localization is a global APD problem. Future studies that employ a case study design might provide more insights.